A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 2 SIMANDOLAK IN COMPREHENDING RECOUNT TEXTS - Nurmania Fitri; Effendy Gultom; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was designed to describe the students’ ability in comprehending recount texts. The aim was to find out the second year students’ ability in comprehending recount texts. This descriptive research took place in SMPN2 Simandolak from April to May 2016. The total population of SMPN 2 Simandolak is 60 students. Thirty students were taken for try out and thirty students were taken for sample of the research by using total sampling. In collecting the data, the writer used 28 questions in the test. The time allotment for doing the test was 60 minutes. The data was analyzed by calculating the students’ individual scores and finding out the mean score. The students’ scores were classified into five levels; they are: excellent, good, mediocre, poor, and very poor. The data was presented by using graphic. Based on the result finding of this research, the second year students’ ability in comprehending Recount texts at SMPN 2 Simandolak was in good level. The mean score of the whole students was 61.4.Key Words: Students’ Ability, Comprehending Recount Texts